PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI, BUDAYA KERJA, DAN INSENTIF, TERHADAP KINERJA KARYAWAN LPD DI KECAMATAN PENEBEL - Kadek Krisyanti Monita; I Ketut Yudana Adi (Universitas Triatma Mulya, 2022)
The formulation of the problem and the purpose of this study is to determine the effect of the effectiveness of accounting information systems, work culture and incentives on employee performance. The location of this research is LPD in Penebel District. The population uses LPD employees in Penebel District and the sample used is 62 respondents. The sample was carried out by purposive sampling method. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t-test and F-test. regression coefficient value is 0.524, t is 3.088 and sig is 0.003. (2) Work culture has a significant positive effect on employee performance, where the regression coefficient value is 0.486, t is .4,514 and sig is 0,000. (3) Incentives have a significant positive effect on employee performance, where the regression coefficient value is 0.326, t is 2.600 and sig is 0.12. The magnitude of the influence of independent variables on employee performance is 53.7%. The suggestion in this research is that LPDs in Penebel District are expected to periodically update the information system used, always be firm in implementing the company's work culture and always provide incentives that are in accordance with employee performance.